p53 is a central regulator driving neurodegeneration caused by C9orf72 poly(PR). - Maor-Nof, M.; Shipony, Z.; Lopez-Gonzalez, R.; Nakayama, L.; Zhang, Y.J.; Couthouis, J.; Blum, J.A.; Castruita, P.A.; Linares, G.R.; Ruan, K.; Ramaswami, G.; Simon, D.J.; et al. (Cell, 2021)
The most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) is a GGGGCC repeat expansion in the C9orf72 gene. We developed a platform to interrogate the chromatin accessibility landscape and transcriptional program within neurons during degeneration. We provide evidence that neurons expressing the dipeptide repeat protein poly(proline-arginine), translated from the C9orf72 repeat expansion, activate a highly specific transcriptional program, exemplified by a single transcription factor, p53. Ablating p53 in mice completely rescued neurons from degeneration and markedly increased survival in a C9orf72 mouse model. p53 reduction also rescued axonal degeneration caused by poly(glycine-arginine), increased survival of C9orf72 ALS/FTD-patient-induced pluripotent stem cell (iPSC)-derived motor neurons, and mitigated neurodegeneration in a C9orf72 fly model. We show that p53 activates a downstream transcriptional program, including Puma, which drives neurodegeneration. These data demonstrate a neurodegenerative mechanism dynamically regulated through transcription-factor-binding events and provide a framework to apply chromatin accessibility and transcription program profiles to neurodegeneration.